Study of the influence of 3D printing parameters on the mechanical properties of PLA - Leite, Marco (2018)
This paper aims to determine the influence of 3D printing parameters, such as Infill Density, Extrusion Temperature, Raster Angle and Layer Thickness, on mechanical properties, namely Ultimate Tensile Strength, Yield Strength, Modulus of Elasticity and Elongation at Break, in the case of polylactic acid (PLA), after it goes through the manufacturing process. Another objective is to study water absorption by the PLA, with a goal to minimize it by means of a coating agent. The influence of each printing parameter on each mechanical property is evaluated by using analysis of variance (ANOVA).